Evaluation of Strength Behavior of Aggregates Mixed with Tire Chips in Granular Piles - Pradeep N.M.; Kumar S.; Shukla S.K. (My University, 2025)
This paper discusses the assessment of optimum mix proportions of aggregates and tire chips based on shear strength and index properties (unit weight and specific gravity) for applications in granular piles/stone columns. Tire chips of cubical size 10 mm × 10 mm × 10 mm and aggregates passing through 12.5 mm, but retained on 10 mm were used. The aggregates and tire chips were mixed using the volumetric mix proportions (aggregates: tire chips) (%) of 100:0, 75:25, 50:50, 25:75 and 0:100. Large direct shear tests under normal stresses of 50, 100, and 150 kPa were performed on these mix proportions. The optimum mixing ratio is a function of void ratio and shear strength of mixture. Based on findings from experiments, the optimum content of tire chips has been found to be 25% by weight, which is equivalent to 44.4% by volume. The results from unit weight and specific gravity tests indicate that the void ratio of the mixture decreased up to the tire chips content of 50% and again increased with 100% content by weight. The results from large direct shear tests have shown that the percentage decrease in shear strength of aggregates due to addition of 25% tire chips by weight is 4.6%. Also, the angle of internal friction slightly decreased by 3° and cohesion value increased by 3.1 kPa due to addition of 25% tire chips by weight. The addition of tire chips enables the aggregate to become ductile in nature, and its dilation value and shear modulus values are decreased. The bearing capacity of granular pile has been defined in terms of improvement factor and loss of improvement is found to be only 12%, but replacement of aggregate with 25% tire chips by weight is the best solution in terms of cost-effectiveness and sustainability. © The Author(s), under exclusive licence to Shiraz University 2023.